JUAL BELI BUAH ALPUKAT SECARA BORONGAN PERSPEKTIF SOSIOLOGI HUKUM ISLAM (STUDI KASUS JORONG LADANG LUNGGUAK BATU NAGARI PAKAN SINAYAN KECAMATAN BANUHAMPU KABUPATEN AGAM) - Tajri, Latifah; Ridha, Sofia (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to analyze the practice of wholesale avocado trading in Jorong Ladang Lungguak Batu, Nagari Pakan Sinayan, Banuhampu District, Agam Regency, from the perspective of Islamic legal sociology. This research employs a qualitative field method using interviews and observations involving avocado tree owners and buyers (pakang). The findings reveal that the wholesale avocado trading practice is conducted orally without written agreements and relies heavily on mutual trust between sellers and buyers. Buyers tend to have greater dominance in determining prices and harvest times, while tree owners hold weaker bargaining positions. From the perspective of Islamic legal sociology, this practice is considered ‘urf (custom) that remains valid as long as it does not lead to injustice; however, in practice, it still contains elements of gharar (uncertainty) and potential socio-economic imbalance. The implication of this study highlights the need to enhance community understanding of Islamic economic law to ensure transactions are carried out based on the principles of justice, consent, and transparency in accordance with Islamic values.